Fit for purpose? A review of guides for gender-equitable value chain development - Stoian, Dietmar; Donovan, Jason A.; Elias, Marlène; Blare, Trent (Practical Action Publishing, 2020)
Since the early 2000s, value chain development (VCD) has figured prominently on the agendas of donors, governments, and NGOs in pursuit of market-based options to poverty reduction, food security, gender equity, and other goals. Researchers have shown interest in value chains as a theoretical construct for studying interactions between farmers and markets, while practitioners have focused their attention on approaches and tools for applying VCD in the field. Despite considerable investments in VCD, limited evidence exists on the extent to which different approaches to VCD have advanced diverse development goals. This knowledge gap sounds alarms, not least because of the complexities involved and the multitude of options for getting it right (or wrong). The 16 chapters in this book offer unique perspectives on VCD from both practitioners and researchers. They explore how VCD is implemented in the field, options for innovation in design, and the potential for VCD to achieve impact at scale. Altogether, the book provides a timely critique of current approaches, pointing at options for more reflexive learning, new collaborative frameworks, and faster innovation of VCD. Here we introduce the chapters and extract some of their principal lessons in terms of the promise, delivery, and opportunities for impact at scale.